PERANCANGAN SISTEM PENAWARAN DESAIN ARSITEKTUR BANGUNAN BERBASIS ANDROID PADA CV. BKAIS : PERANCANGAN SISTEM PENAWARAN DESAIN ARSITEKTUR BANGUNAN BERBASIS ANDROID PADA CV. BKAIS - Pratama, Rizki; Nugraha , Iqbal Nauval; Gustona, Fairon (Jurnal Media Informatika dan Teknologi, 2023)
Android is open source, allowing anyone to create applications for Android and sell them on the Play Store. The increasing number of smartphone users today has led to a growing development of Android-based applications, making them easily accessible on each smartphone. CV. BKAIS, as a company in the field of architecture, recognizes the importance of keeping up with the latest technology trends to enhance the architectural design and offering processes. Therefore, an Android-based architectural design proposal system is considered a relevant and innovative solution to be implemented at CV. BKAIS. The conclusion drawn from this research is that the Android-based complaint service application is designed using the Java programming language and Android Studio. The architectural design proposal application is designed to facilitate customers in finding architectural design references when they want to construct a building. Additionally, the application design incorporates a user-friendly interface, and the Android-based architectural design proposal application is created with the goal of providing users with a quick and efficient design search process that is designed to be highly effective and efficient.